A STUDY ON INFLUENCE OF SUPPLY CHAIN STRATEGIES ON COMPETITIVE ADVANTAGE OF TEXTILE INDUSTRY – AN INTEGRATED MODEL - Vanathy, R; SWAMYNATHAN, R (Journal of Contemporary Research in Management (JCRM), 2017)
This research paper represents one of the first empirical efforts to explore the complex causal relationships within the textile supply chain of south India. The research focuses on the textile industry’s supply Chain Collaboration, Business Process Orientation, Supply Chain Pressure and Competitive Advantage with special geographical reference to Erode, a major hub of textiles in Tamilnadu, South India. The need for this study had risen from various literature reviews and industry associations’ demand by which the researcher had understood the importance of the study and its industry implications. The study has adapted a descriptive design and the data were collected both from primary and secondary sources. A structured questionnaire was developed, validated and administered for the primary data. Valid and reliable measures of Supply chain strategies, mitigation of supply chain pressure and their impact on competitive advantage were studied. The instrument development process involved structured interviews, a pilot survey and a large –scale survey. The large scale survey yielded 235 responses from registered textile supply chain partners-cloth manufacturers, wholesalers and retailers who are the members of Erode cloth merchant association, the largest association textile traders in South India. Exact statistical methods were used to asses and validate the constructs. The methods were: reliability, and structural equation modeling. An integrated model was developed and tested using structural equation methodology. The research findings support the notion that higher levels of Supply chain strategies will lead to improved Competitive advantage and mitigate the supply chain pressure. The strategies studied with reference to textile industry are supply chain collaboration and business process orientation. A SEM model with R2 value 0.407 is derived.